Mixed DPPC/POPC Monolayers: All-atom Molecular Dynamics Simulations and Langmuir Monolayer Experiments - Olżyńska, Agnieszka; Zubek, Michal; Roeselova, Martina; Korchowiec, Jacek; Cwiklik, Lukasz (Biochimica et biophysica acta, 2016)
To elucidate the consequences of the saturated-unsaturated nature of lipid surface films, monolayers formed by an equimolar mixture of 1-palmitoyl-2-oleyl-sn-glycero-3-phosphocholine (POPC) and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) lipids are investigated in a wide range of surface pressures. As such mixtures share some features with naturally-occurring surfactants, for example the lung surfactant, the systems are studied at the temperature relevant for human body. All-atom molecular dynamics simulations and Langmuir trough experiments are employed. The binary lipid mixture is compared with the corresponding one-component systems. Atomistic-level alterations of monolayer molecular properties upon lateral compression are scrutinized. These involve elevation of lateral ordering of lipid chains, modulation of chain and headgroup orientation, and reduction of lipid hydration. The presence of the unsaturated POPC in the DPPC/POPC mixture reduces the liquid expanded-liquid condensed coexistence region and moderates the phase transition. Simulations predict that nanoscale lipid de-mixing occurs with small transient DPPC clusters emerging due to local fluctuations of the lateral lipid arrangement. A vertical sorting of lipids induced by lateral compression is also observed, with DPPC transferred toward the water phase. Both the conformational lipid alterations due to monolayer compression as well as the existence of lateral dynamic inhomogeneities of the lipid film are potentially pertain to dynamic and non-homogeneous lipid interfacial systems.
Keywords: Lipids; molekulární konformace; Molecular Conformation; simulace molekulární dynamiky; Phosphatidylcholines; lipidy; Lung surfactant; Molecular dynamics; Molecular Dynamics Simulation; 1,2-dipalmitoylfosfatidylcholin; Langmuir trough; 1,2-Dipalmitoylphosphatidylcholine; Phospholipid monolayers; fosfatidylcholiny